2020
DOI: 10.20961/ijie.v4i2.40021
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Nomophobia as a Predictor of Smartphone Addiction among Nigerian Pre-service Mathematics Teachers

Abstract: Nomophobia and smartphone addiction are behavioural disorders that are maladaptive and affect 21<sup>st</sup>-century digital natives anywhere, everywhere. This study investigated nomophobia as a predictor of smartphone addiction among Nigerian pre-service mathematics teachers within the framework of quantitative methodology of non-experimental correlational research design. The participants consisted of 300 pre-service mathematics teachers randomly selected from the Department of Science and Techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Research has shown that problematic smartphone use is related to impulsivity (Contractor et al, 2017;De-Sola et al, 2017;Harris et al, 2020;Horvath et al, 2020;Tugun et al, 2020), impaired attention (Harris et al, 2020;Rezaee & Pedret, 2018;Roberts et al, 2015), and compromised inhibitory control (Chen et al, 2016; 3 / 14 Harris et al, 2020;Vezzoli et al, 2021).In recent years, academics and public health practitioners have focused more emphasis on problematic smartphone use such as smartphone addiction and nomophobia (fear of being detached from mobile phone connectivity). According to Awofala (2020), nomophobia is one of the predictive variables of smartphone addiction. However, given the idea of problematic smartphone use's relatively recent development as a research subject, definitions of the term are continually developing.…”
Section: According To American Society Of Addiction Medicine (Asam)mentioning
confidence: 99%
“…Research has shown that problematic smartphone use is related to impulsivity (Contractor et al, 2017;De-Sola et al, 2017;Harris et al, 2020;Horvath et al, 2020;Tugun et al, 2020), impaired attention (Harris et al, 2020;Rezaee & Pedret, 2018;Roberts et al, 2015), and compromised inhibitory control (Chen et al, 2016; 3 / 14 Harris et al, 2020;Vezzoli et al, 2021).In recent years, academics and public health practitioners have focused more emphasis on problematic smartphone use such as smartphone addiction and nomophobia (fear of being detached from mobile phone connectivity). According to Awofala (2020), nomophobia is one of the predictive variables of smartphone addiction. However, given the idea of problematic smartphone use's relatively recent development as a research subject, definitions of the term are continually developing.…”
Section: According To American Society Of Addiction Medicine (Asam)mentioning
confidence: 99%